Rape investigation handbook (Elsevier Academic Press, 2005)
This work addresses specific investigative and forensic processes related to sex crimes for those who work in law enforcement, the defense community, or in the private sector. It is an unprecedented collaborative work -- the first working manual for sex crime investigators, written by sex crime investigators and forensic scientists.